Deployment risk and resilience model applied to military children - Santos, Renato Pessoa dos (2022)
This exploratory study investigates the impact of a military mission on Portuguese families, specifically on children. Although most research seeks the negative consequences of this lived experience, through the “Deployment Risk and Resilience Model” the present study intends to explore if this period can also be an opportunity for military’s children to grow and become more resilient. Aiming to express freely their lived and felt stories about the phenomenon under study, semi-structured interviews were conducted with 22 children of the service members of the Portuguese Army, aged between 8 and 21 years old. The results of the thematic analysis indicated that the most critical moments of the mission were the notification period, the last days before the departure of the service member, and the deployment. The preparation of activities for the service members’ absence in the pre-deployment and the increase of tasks to be carried out, during the deployment, were the most referenced changes. In the post-deployment, children perceived a rapid readjustment of the family system. Despite the military's children's difficulties in readjusting during the mission, they reported that the feelings of closeness to the nuclear family, increased responsibility, and personal growth were positive results experienced. It would be interesting to extend similar studies within family systems, as in other branches of the armed forces. As practical implications, the findings of our pioneering study may significantly contribute to the construction of programs and/or actions that promote a possible growth in the personal resilience of the children of Portuguese service members, and not only the recovery of the state prior to the mission.